Sodium channels of SCNIA gene mutations in generalized epilepsy with febrile seizure plus (GEFS+) spectrum related to autism - Elisabeth Herini; Yudha Patria; Gunadi Gunadi; Surini Yusoff; Indra SAri Kusuma Harahap; Sunartini Sunartini; Sutaryo Sutaryo; Satoshi Takada; Hisahide Nishio (Indonesian Pediatric Society, 2010)
Background Mutations in the a-subunit of the first neuronalsodium channel gene SCNIA have been demonstrated forgeneralized epilepsy lith febrile seizures plus (GEFS+), severemyoclonic epilepsy in infancy (SMEI), and borderline SMEI(SMEB). SCNIA mutations are also described in patients 'Withpsychiatric disorders such as autism.Objective To identify the mutations of SCNIA gene in patientswith GEFS+ spectrum which may be related to autism.Methods We examined four patients v.ith autism and GEFS+spectrum who were admitted to the Department of Child Health,Sardjito Hospital, Yogyakarta, Indonesia. Diagnosis of autism wasbased on DSMô€ŸIV;ICD X criteria. Mutations in SCNIA wereidentified by PCRamplification and denaturing highô€Ÿperformanceliquid chromatography analysis, Mth subsequent sequencing.Results There were four patients, all boys, aged 1.8 year to 7 years.The phenotypes of epilepsy were GEFS+ in one patient, SMEBin one patient and SMEI in two patients. Sequencing analysisrevealed a Gô€Ÿtoô€ŸA heterozygous transition which was detectedat nucleotide c.4834G>A (p.V1612I ) in exon 25. Other singlenucleotid polymorphisms (SNPs) were c.383 +66T>C in intron 2,c.603-91G>A and c.603-1060> T in intron 4, c.965-21C> T inintron 6, c.1028+21T>Cin intron 7, c.2173G>A in exon 12 andc. 2177-38C>A, c.2177-12delT, c.2176+44C> T in intron 12.Conclusion In this study, we reported the first cases Mth mutationin SCNIA gene in GEFS+ spectrum related to autistic patientsin Indonesian population, which showed a missense mutationp.V16121. [Paediatr lndones. 2010;50:125-32].